2009
DOI: 10.1369/jhc.2009.954636
|View full text |Cite
|
Sign up to set email alerts
|

The Maturation of Oocyte Follicular Epithelium of Podarcis s. sicula Is Promoted by d-Aspartic Acid

Abstract: We investigated whether the maturation of oocyte follicular epithelium of lizard is affected by d-aspartic acid (d-Asp). Our results demonstrated that d-Asp is endogenously present in the oocytes, and its distribution varies during the reproductive cycle and following intraperitoneal administration. At previtellogenesis, it is observed in the cytoplasm and nucleus of pyriform cells, in intermediate cells, in some small cells of the granulosa, in the ooplasm, and in some thecal elements. At vitellogenesis, d-As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…The results of present study agree with those obtained in lizard P. sicula [13][14][15] in which the administration of d-Asp causes in the female a decrease in testosterone content, while favoring in the male an increase of the androgen level. In the female lizard, the physiological mechanism underlying the inverse and direct relationship between d-Asp and sex steroid hormones was elucidated in our previous in vitro studies [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of present study agree with those obtained in lizard P. sicula [13][14][15] in which the administration of d-Asp causes in the female a decrease in testosterone content, while favoring in the male an increase of the androgen level. In the female lizard, the physiological mechanism underlying the inverse and direct relationship between d-Asp and sex steroid hormones was elucidated in our previous in vitro studies [13].…”
Section: Discussionsupporting
confidence: 91%
“…Our research group has focused some studies on the role of d-Asp in the gonads of the lizard, Podarcis sicula, a seasonal breeding vertebrate. In lizard female, d-Asp enhances follicular production of 17␤-estradiol by up-regulating the local aromatase activity [13] and also promotes the maturation of oocyte follicular epithelium [14]. Furthermore, it has been demonstrated that d-Asp is rapidly taken up by Leydig cells of injected lizards and its rise is coupled with a significant increase in testosterone levels with a consequent augment of mitotic activity of the germinal epithelium of the testis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in seasonally reproductive vertebrates, the morphology of gonads changes as a function of reproductive processes. A representative example in this sense is the lizard P. sicula , whose features have been already studied by our group (Assisi et al, 2001; Raucci and Di Fiore, 2010). …”
Section: Discussionmentioning
confidence: 93%
“…D-aspartic acid (D-Asp) is a D-amino acid that has received significant attention because of its presence in animal nervous and reproductive systems (D’Aniello and Giuditta 1977; Dunlop et al 1986; Fisher et al 1991; Hashimoto et al 1993; D’Aniello et al 1996; Schell et al 1997; D’Aniello 2007; Homma 2007); however, questions about its metabolism, cellular function, biological and physiological roles, and pathological significance remain. Investigations of D-Asp in living organisms have involved various animals, including cephalopods (D’Aniello and Giuditta 1977; D’Aniello et al 1995b; D’Aniello et al 2011), gastropods (D’Aniello et al 1993b; Shibata et al 2003; Miao et al 2006a; Spinelli et al 2006), amphibians (Di Fiore et al 1998; Raucci and Di Fiore 2011), reptiles (Assisi et al 2001; Raucci and Di Fiore 2010), and mammals, including humans (Fisher et al 1991; Hamase et al 1999; Morikawa et al 2007). These studies document its widespread occurrence and suggest that D-Asp plays important roles throughout the Metazoan.…”
Section: Introductionmentioning
confidence: 99%